Numerical modelling of an enhanced perpendicular transport regime in the scrape-off layer of ASDEX Upgrade. (25th May 2021) - Zito, A; Wischmeier, M; Carralero, D; Manz, P; Paradela Pérez, I; Passoni, M
Abstract: A desirable scenario for future fusion devices is one in which dissipative processes in the scrape-off layer (SOL) are maximized, aiming to detach the divertor plasma. The access to such a regime in current devices is thought to be correlated to the increase of the perpendicular particle transport in the SOL. In this work we investigated numerically how increasing perpendicular transport globally affects the SOL plasma through the SOLPS-ITER code package. For this we modelled one L-mode discharge, performed at the ASDEX Upgrade tokamak, trying to obtain the most accurate fit to the experimental data at the outer midplane. Studying the plasma solutions and analyzing the resulting momentum and power balances in the SOL allowed to characterize how enhancing perpendicular SOL transport leads to the experimentally observed phenomena, i.e. the formation of a density shoulder at the midplane and the partial detachment of the divertor plasma. The results suggest that strong momentum losses caused by the increase of transport are able to explain the qualitatively observed detachment in the modelled discharge. The concurrent enhanced ionization of neutrals resulting from divertor recycling, triggered by an increase of radial energy transport in the SOL, can be invoked as a cause for the shoulder formation.